THE IMPORTANCE OF INTERACTIVE METHODS IN DEVELOPING DISCURSIVE COMPETENCE AMONG HIGHER LEVEL STUDENTS - Rustamova Dilobar (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article analyzes the role and significance of interactive teaching methods in developing discursive competence among senior school students. It explores the concept of discursive competence, defines its relevance in the educational context, and presents practical techniques such as debates, brainstorming, and role-playing games. These methods enhance students’ independent thinking, critical reasoning, oral and written expression, and their ability to engage in effective communication. The study emphasizes how such interactive approaches not only improve language skills but also contribute to students’ social activity and personal growth in real-life situations.